Internal information quality and performance metric selection - Guay, Wayne; Kim, Chongho; Timmermans, Oscar (Journal of Accounting and Economics, 2026)
We examine the role of firms’ internal information quality (IIQ) in designing executive incentive contracts. We find that higher IIQ is associated with a greater number of performance metrics and increased dissimilarity from peer firms’ contracts, particularly along non-financial dimensions. These relations hold when we examine changes in IIQ that are likely induced by plausibly exogenous shifts in two financial accounting standards. We further find that incorporating more numerous and more dissimilar non-financial metrics is positively associated with future profitability, but only when IIQ is high. Our results are consistent with the hypothesis that the quality of a firm’s internal information is a friction in performance metric selection.